Development Of Instagram-Based Microblog Learning Media On High School Buffer Solution Material - Fani Ahmat Tri Alfitra; Zurweni Zurweni; Firdiawan Ekaputra (Mathematics Education Study Program, 2025)
This research is included in Research and Development (R&D) research which aims to develop Instagram-based microblog learning media with buffer solution material that is valid, feasible and practical. This development research uses the Lee & Owens development model which consists of the analysis design, development, implementation and evaluation. This research was carried out at SMAN 1 Muaro Jambi with research subjects namely class, student and teacher response questionnaires. Data validation and distribution of questionnaires were carried out using qualitative descriptive analysis. Based on the research results, the learning media developed has been tested as highly valid by material expert validators with a validity percentage of 84.4% and media experts at 92%. Furthermore, learning media is also very practical for students to use with a practicality percentage of 91% and a practicality percentage from teachers of 89%. From the research results it can be concluded that the media developed is suitable for use in the chemistry learning process, especially buffer solution material.